Comparative methods in practice : Using an iterative approach to explore aviation apprenticeships in England and Germany - Li, Junmin [Verfasser]; Lahiff, Ann [Verfasser]; Unwin, Lorna [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2020)
"In international comparative vocational education and training (VET) research, the discourse concerning the interlinking of theory and empirical practice often runs in one direction and asks: to what extent the theoretical concepts shape the empirical research design. The empirical limitations and challenges of field-based research rarely find their way into the theoretical debate. This is despite the particularly important challenges that need to be faced during field research in comparative VET to prevent misinterpretation and ethnocentrism. This chapter expands the discourse and outlines an iterative, reflective approach to interlink theoretical frameworks and empirical work through an explorative study of aviation apprenticeships in England and Germany. This study set out to examine the impact of international technical standardisation and regulation on the design, organisation and delivery of apprenticeships in the aeronautical and aerospace sectors in England and Germany. We identify the challenges we met during the empirical stage of the research and discuss the ways in which our responses influenced our theoretical elaboration." (author's abstract ; BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 1.5 International vergleichende Berufsbildungsforschung; S 6.4.2.1 Verkehrsberufe (inkl. Nachrichtenverkehr); I 2.1 Deutschland; I 2.2.1 Westeuropa; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Luftverkehrsberuf; Forschungsansatz; Empirische Sozialforschung; Bundesrepublik Deutschland; England